2020
DOI: 10.1002/jbm.a.37103
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds from Leea macrophylla enhance phagocytosis and promote osteoblasts differentiation by alkaline phosphatase, type 1 collagen, and osteocalcin gene expression

Abstract: The current study investigated the immunomodulating and osteoblast differentiation potential of the natural compounds from Leea macrophylla (LMN). Immunomodulatory effects have been investigated by the phagocytosis of Candida albicans using polymorphonuclear neutrophil cells in the in vitro slide method. A bioactivity‐guided fractionation technique was used to evaluate the stimulating effect of L. macrophylla methanol extract on osteoblast differentiation using mouse osteoblastic cells. A low dose of LMN was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Thus, this inspection helps to figure out the functional groups that have the inclination to reduce silver ions and wrap up the bio-reduced LM-AgNPs. It was reported that the extract of LM leaves was rich in phenolic and flavonoid contents and the compounds had been spotted in methanol extract of Leea macrophylla by GC–MS [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this inspection helps to figure out the functional groups that have the inclination to reduce silver ions and wrap up the bio-reduced LM-AgNPs. It was reported that the extract of LM leaves was rich in phenolic and flavonoid contents and the compounds had been spotted in methanol extract of Leea macrophylla by GC–MS [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The expression of the osteogenic marker gene ALP bolsters concomitantly with the expression of the RUNX2 gene [ 30 , 31 ]. ALP facilitates the synthesis of new collagenous matrix and the release of matrix-bound vesicles to regulate matrix mineralization by the osteoblasts [ 32 ]. Upon matrix encapsulation, the osteoblasts transform into osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…ALP activity was used to characterize autophagy levels [ 37 ]. In Saccharomyces cerevisiae , the precursor of ALP in cytoplasm is encapsulated in autophagosomes and then transported to vacuoles, in which it can be degraded by enzymes.…”
Section: Discussionmentioning
confidence: 99%